KEMAMPUAN UJI TABUNG WIDAL MENGGUNAKAN ANTIGEN IMPORT DAN ANTIGEN LOKAL - Puspa Wardhani; Prihatini Prihatini; Probohoesodo M.Y (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2005)
Despite of its higher specificity than Widal-slide test, Widal-tube test is not widely used by medical laboratories because it is not practical and each laboratory has to produce their own antigens. The Laboratory must have sufficient microbiology equipments and reagents to produce antigens. REMEL® provides ‘ready for use’ antigens to perform Widal-tube test. To Compare and correlate Widal-tube test using REMEL® imported antigens and local antigens (produced by lab. Clinical pathology Dr. Soetomo hospital). The samples were tested by Widal-tube test, using REMEL® and local antigens, comparing Salmonella typhi (ST) O antigen, ST H antigen, S. paratyphi (SP) A H antigen, and SP B H antigen for each method, with twofold dilution from 1/40 until 1/1280. The number of samples was 55. The results are defined as pathologic (above cut-off value) and non pathologic (below cut-off value). REMEL® ST O antigen had a significant correlation to local antigens (r = 0.665, p < 0.01). REMEL® ST H antigen also had a significant correlation to local antigen (r = 0.671, p < 0.01), REMEL® SP B H has no significant correlation to local antigen (r = 0.389, p < 0.01). All samples (55) showed negative results (non pathologic) using SPA H local antigen. When using REMEL® SPA H antigen, 51 were non pathologic and 4 were pathologic. Widal-tube test using REMEL® antigens has significant correlation with local antigens so it might be considered to be used for diagnosing typhoid fever.